Kinematic and Kinetic Analysis of Rolling Motion in Normal Adults - Takahashi, Masaaki; Sekiya, Noboru (Journal of the Japanese Physical Therapy Association, 2004)
The purpose of this study was to describe a rolling motion, which is common in normal adults and patients with motor disorder, and to try to understand the mechanism of the motion. Ten healthy young adults participated in the experiment and were requested to roll from supine to side-lying by pressing the floor with their contra-lateral foot. Their motions in the task were measured with a 3-D analysis system and a force platform. The hip abduction-adduction angle was at around the neutral position and was approximately constant throughout the rolling motion. The hip rotation angle was at a neutral or slightly internally rotated position at the beginning of the motion, and it externally rotated linearly toward the end of the rolling motion. These patterns were thought to be mechanically the most effective for the subjects to perform the motion as was also indicated by the kinetic analysis.